PERILAKU LESBIAN DALAM MEMPERTAHANKAN PASANGAN DI TEMPAT KOST DI KELURAHAN PULAI ANAK AIR BUKITTINGGI - FIFI, ELENDA KOEISMA (Pendidikan Sosiologi, 2014)
Adolescent a represent a period of very labile in seeking of spirit. this Transition Priode often cause various problem of nymph that happened in town of Bukittinggi there is woman braiding relation with one who is same gender because feeling to like, balmy with woman humanity couple which always use feeling and liver in braiding relation, found by four women ( two tide) experiencing relationas Iesbian that is taking a fancy to type humanity. Is therefore formulated by problems like behavior of Iesbian in maintaining couple in place board with.Theory which is used in this research is to social action of Max Weber, with research qualitative which is interpreted as understanding of what felt by others, comprehending pattern of piker others viewpoint and and descriptive research type. As for informan in this research is Iesbian couple by using technique of snowball sampling. Informan amount to four people ( two tide). Data type the used is primary data and data of sekunder. Method data collecting conducted with three way of: (1) observation (moderating participation), (2) interview, (3) documentation. Unit analyse data the used is individual with data analysis of Miles & Huberman which consist of discount phase, presentation of data analysis or data and withdrawal of conclusion.Result of research indicate that behavior in maintaining relation with couple is : 1) activity with 2) each other trusting 3) solving of problem and communications 4) romantic